(untitled) (Community Based Medical Journal, 2025)
A cross-sectional study was conducted in the Department of Dermatology and Venereology, Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, Bangladesh, between March 2022 and March 2024, to evaluate the epidemiology of autoimmune bullous diseases (AIBDs). A total of 89 patients diagnosed with autoimmune bullous diseases (AIBDs) were enrolled in this study using a purposive sampling method. All demographic and clinical information was documented. Most of our participants were aged 60 years or older (53.9%). A male predominance was observed (59.6%). The most prevalent type of AIBD was pemphigus vulgaris (59.6%). Hypertension (12.4%), diabetes mellitus (7.9%), hyperlipidemia (5.6%), osteoporosis (4.5%), coronary heart disease (3.4%) and hepatitis (3.4%) were observed as the main comorbidities. In nearly three-fourths of the cases (74%) only oral mucosal involvement was identified, while only nasal (2%), only genital (8%), and both oral and genital (16%) mucosal involvement were also observed. Overall, our data showed that the older male population is mainly prone to autoimmune bullous diseases (AIBDs) in Bangladesh. CBMJ 2025 January: Vol. 14 No. 01 P: 134-138